METAFORA DALAM CAKEPAN TEMBANG -TEMBANG JAWA (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
The problem of metaphor is the reality of creative power of language and in the metaphor there is something spoken and compared. There is a distance between tenor and vehicle which is very interesting. The more distant the tenor and vehicle, the more expressive the meaning of metaphor is. There are four kinds of metaphors; they are anthropomorphic, animal, abstract to concrete and the opposite, and sinesthetic. These kinds of metaphor are for knowing how the perception about static space predicted as human being, animal or other creatures and there is the change of concept causing the resemblance of the perceptual and physical meanings. Metaphor is still interesting for the linguists because it is viewed as a process of transference between two conditions or experiences based on the association of each others. Several kinds of the metaphor are found in lyric of Java’s tembangs. They are tembang gedhe, tengahan, macapat, maupun tembang dolanan Kata kunci : ekspresif, cakepan, tembang Jawa